Diagnostic value of determining the level of purine metabolism intermediates in pregnant women with chronic hypertension and superimposed preeclampsia - Dinara Omertayeva; Olga Ponamaryova; Zhanna Amirbekova; Dmitriy Vazenmiller; Miras Mugazov (Society of Diabetic Nephropathy Prevention, 2021)
Introduction: Chronic hypertension and related cardiovascular diseases are some of the leading causes of maternal and perinatal morbidity and mortality in the world. Objectives: The aim of the study was to evaluate the diagnostic value of purine metabolism products in plasma and blood erythrocytes in pregnant women with chronic hypertension with superimposed preeclampsia. Patients and Methods: Around139 patients were examined, including 110 pregnant women and 29 healthy non-pregnant women of childbearing age (control group). The content of purine metabolism intermediates was determined; guanine, hypoxanthine (HX), adenine, xanthine (X) and uric acid (UA) - in plasma and erythrocytes. We also determined the level of blood platelets, proteinuria in the general analysis of urine in pregnant women with chronic arterial hypertension, severe preeclampsia, and in pregnant women with chronic hypertension with superimposed preeclampsia. Results: The level of purine catabolism intermediates significantly exceeds in the blood of pregnant women with chronic hypertension and superimposed preeclampsia compared to control group. It was determinate that purine intermediates a significant increase in pregnant women with chronic hypertension with superimposed preeclampsia compared to pregnant women with isolated chronic hypertension, pregnant women with severe preeclampsia. An analysis of correlations showed that the increase in purine intermediates in blood in pregnant women with chronic hypertension and superimposed preeclampsia is associated with an increase in proteinuria and thrombocytopenia. It indicates a diagnosis of preeclampsia to chronic hypertension. It can be an additional diagnostic criterion, along with proteinuria and thrombocytopenia. Conclusion: Determination of purine intermediates can be used as an additional diagnostic criterion in pregnancy with chronic hypertension.